Choices for America in a Turbulent World Strategic Rethink - Dobbins, James (RAND Corporation, 2015)
The first in a series exploring the elements of a national strategy for U.S. foreign policy, this book examines the most critical decisions likely to face the next president. The book covers global and regional issues and spotlights the long-term policy issues and organizational, financial, and diplomatic challenges that will confront senior U.S. officials in 2017 and beyond.